Induced ruminative and mindful attention in everyday life: an experimental ambulatory assessment study - Huffziger, Silke; Ebner-Priemer, Ulrich; Eisenbach, Christina; Koudela-Hamila, Susanne; Reinhard, Iris; Zamoscik, Vera; Kirsch, Peter; Kühner, Christine (Journal of behavior therapy and experimental psychiatry, 2013)
Background and objectives - Rumination has been proposed as a risk factor for depression, while mindful attention might be protective. Differential effects of these attention foci have so far only been examined in the laboratory. Therefore, we conducted an experimental ambulatory assessment study using ruminative and mindful attention inductions in everyday life to examine their effects in a natural context. - Methods - Fifty young adults carried palmtops over three weekdays (rumination induction day, mindful attention induction day, noninduction day; randomized cross-over design). Ten times a day, participants rated ruminative self-focus and mood. On the induction days, they were additionally subjected to 3-min inductions of ruminative or mindful attention at each assessment. - Results - The two induction modes exhibited differential immediate effects on ruminative self-focus and mood. While induced rumination immediately deteriorated valence and calmness, induced mindful attention specifically enhanced calmness. Depressive symptoms did not moderate these effects. While overall longer term effects of the inductions were missing, the mindful attention day was associated with slightly increasing positive valence over the day. - Limitations - The results need to be replicated in high-risk and patient samples to demonstrate the clinical significance of identified effects. - Conclusions - Results confirm the emotional relevance of rumination and mindful attention in real world settings. Future work may test whether adaptive attention-focusing instructions delivered in daily life can support clinical interventions.
Gesehen am 22.12.2021